Frequency of Pre-Eclampsia in Obese pregnant Females taking Metformin during Pregnancy - Rabia Wajid, Zainab Zubair, Asia Parveen, Amara Jamil, Somer Masood (Pakistan Journal of Medical & Health Sciences, 2023)
Background: It has been shown that obesity takes its roots in the womb. Maternal obesity has an association with macrosomia and the risk of obesity late in life.Obese women who have weight loss before pregnancy may have better pregnancy outcomes if excessive weight gain is avoided during pregnancy. Aim: To determine the frequency of pre-eclampsia in obese pregnant females taking metformin during pregnancy. Methods: It was a Descriptive case series conducted at Unit 1, Department of Obstetrics & Gynecology, Lady Willingdon Hospital, and Lahore from 16-11-21 to 16-5-2022. Non-probability, consecutive sampling was done.165 females fulfilling the selection criteria were included in the study. Informed consent in written form was obtained. If BP was 140/90mmHg, a urine sample was obtained and proteinuria was detected by dipstick method. If proteinuria was present with high blood pressure, then pre-eclampsia was labeled (as per the operational definition). All patients were followed till delivery.Proformas were used for collecting data which was analyzed statistically using SPSS version 20. Results: Participants had a mean age of 28.73±6.71 years, 53(24.65%) females were nulliparous. The mean gestational age of the females was 29.91±5.86 weeks. The mean BMI of the females was 33.12±1.75 kg/m2. In our study, preeclampsia was found in 18(8.37%) obese pregnant females using metformin. Practical implications the correction of diabetes would help in the prevention of preeclampsia in our population. Conclusion: According to this study approximately one-tenth (8.4%) of obese females developed preeclampsia taking metformin during pregnancy. Keywords: Metformin, Pregnancy, Obese, and Preeclampsia, nulliparous, macrosomia